Exposure to interpersonal racism and avoidance behaviours reported by Aboriginal and Torres Strait Islander people with a disability. Issue 4 (28th August 2020) - Temple, Jeromey B.; Wong, Heather; Ferdinand, Angeline; Avery, Scott; Paradies, Yin; Kelaher, Margaret
Abstract: Using the National Aboriginal and Torres Strait Islander Social Survey, this paper examines exposure to interpersonal racism and avoidance reported by Aboriginal and Torres Strait Islander people with disabilities. We find that in 2014–2015, 32 per cent of people aged 15–64 without a disability experienced racism compared with 42 per cent of those with a disability. Half of those living with an intellectual or psychological disability reported racism, and about 20 per cent of those with any disability avoided settings such as healthcare, education or the general public due to past instances of racism, relative to 11 per cent of those without a disability. After adjusting for confounding factors and complex survey design, presence of a disability was associated with a 1.6–1.8 odds increase in exposure to racism, more frequent racist exposure and avoidance. Disability was further associated with an approximate doubling of the odds of reporting multi‐context avoidance and the likelihood of reporting both racism and avoidance in tandem. Severity of disability, higher numbers of disabling conditions and specific disability types were associated with increased odds of racism and avoidance. Independent of these effects, removal from one's natural family and identifying with homelands was strongly associated with racism and avoidance.